Analysis of Water-saving Potential and Contribution Rate of Beverage Manufacturing Industry in Beijing - GAO Yuan; ZHENG Shasha; ZHANG Chunling; FU Yicheng (Renmin Zhujiang)
Among the various industrial industries in Beijing,the beverage manufacturing industry has relatively low water use efficiency and is also a major industrial water user in Beijing.For the implementation of the new development concept and the construction of a water-saving city,the economical and intensive utilization of water resources in Beijing has put forward new requirements on regional industrial development.Regarding the incomplete calculation theory and the lack of a core calculation method for the water-saving potential of the beverage manufacturing industry in Beijing,this paper studies the ways to further water saving for the beverage manufacturing industry on the basis of analyzing the current production and water consumption situations of the beverage manufacturing industry in Beijing.Furthermore,the theoretical support for the water-saving potential is explored,and a calculation model is built to scientifically analyze the water-saving potential and contribution rate of product structure adjustment and water use efficiency improvement of the industry.The research shows that the three major beverage products in Beijing,namely carbonated beverages (soda),packaged drinking water,and fruit and vegetable juice beverages,have 3.32 million m3 of water-saving potential,and the water-saving contribution rate of water use efficiency improvement reaches 97.4%,indicating that the production structure of the industry can be further optimized and adjusted.The research results can facilitate Beijing to implement the “National Water Conservation Action Plan” and ultimately contribute to the construction of a water-saving society.